IMPLEMENTASI KEBIJAKAN RETRIBUSI PARKIR DI KABUPATEN MERAUKE - Apolus Betaubun (SOCIETAS, 2015)
ABSTRACTIn the frame work of the implementation of regional autonomy today, the main goal is that local governments can manage all there sources available in the area in accor and cewith the mandate of Law Number 32 Year 2004 on Regional Government.The aimof there search was to  find out to what extent the implementation of parking retribution policy in Merauke Regency do neby Transportation Dapartment of Merauke Regency.There search was a descriptive qualitative study. The data were  obtained trough in-depth interview and observation.The result so there search indicate that there are somethings which do no trun well. They are the lack of human resources as the field execut or sand supervisors. Besides, parking attendants' behavior is not in accord an cewith expectation. In relation to this,it is necessary to give training to officials mainly to particular unit which handles parking issues and to add the number of control of ficials as well to control the undisciplined parking attendants in carrying out their task.